86.2k views
25 votes
The sum of all the solutions of the equation: (10x − 3a )(3x + 39)(5x − 3) = 0 is (

− 1).
Find a.

Please help!!

2 Answers

2 votes

2627828818182-718818288281-288181991_2792901=72892992

User MarkPlewis
by
4.7k points
10 votes

Answer:


(10x - 3a)(3x + 39)(5x - 3) = 0 \\ dealing \: with \: (10x - 3a) \: and \: (5x - 3) \\ (10x - 3a)(5x - 3) = 0 \\ 50 {x}^(2) - (30 + 15a)x + 9a = 0 \\ sum \: of \: the \: equation \: = (30 + 15a) = - 1 \\ 15a = - 31 \\ a = - (31)/(15)

User Sixto Saez
by
5.3k points